Penggunaan Video Interaktif Untuk Meningkatkan Hasil Belajar Materi Keragaman Budaya Lingkungan Sekitar Siswa Kelas IV B SDN Pakis I Surabaya - Puri Eka Febrianti; Bekti Wirawati; Nunuk Suliyastuti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to improve students' learning experience in Pancasila education through interactive video media at SDN 1 Pakis Surabaya. The research used a spiral-based PTK method with a total of 25 students, with a focus on planning, action, observation and reflection. The research results show a significant increase in, student learning outcomes after video interactivity. This research shows that the use of interactive videos in the Pancasila education program at SDN 1 Pakis Surabaya significantly improves student learning outcomes. Based on the data collected, it appears that the use of interactive videos can improve students' understanding of the material, especially on teacher-led learning topics that prioritize good behavior in the surrounding environment. The increase in learning outcomes as seen from the average student score from 68 to 75 shows that this media is effective in helping students meet the Minimum Completion Criteria (KKM) that have been set. with a percentage in the initial condition of 41%, in cycle I which was proven to be 83%, and the percentage in cycle II was 100%. In addition, every student succeeded in achieving the learning objectives in cycle II, with a statistically significant average increase. Observations also showed that student activity and motivation increased, indicating that interactive videos had a positive impact on both academic performance and behavior.